2021
DOI: 10.1007/s00167-021-06771-w
|View full text |Cite
|
Sign up to set email alerts
|

Low grade of osteoarthritis development after Latarjet procedure with a minimum 5 years of follow-up: a systematic review and pooled analysis

Abstract: Purpose The purpose of this systematic review and pooled analysis was to evaluate incidence and risk factors for glenohumeral osteoarthritis (OA) in patients who underwent Latarjet procedure with a minimum of 5-year follow-up. Methods The PRISMA guidelines were followed to perform this systematic review. PubMed and EMBASE were searched up to February 29, 2020 for English, human in vivo studies that evaluated glenohumeral OA in patients undergoing Latarjet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 64 publications
(95 reference statements)
0
11
0
Order By: Relevance
“…The post-operative range of motion after bony stabilization of the glenoid has been under debate lately [25,31] patients after open Latarjet procedures [12]. Additionally, a biomechanic evaluation by Giles et al demonstrated a significant loss of high external rotation after Latarjet procedures in a cadaveric model when the conjoint tendon was loaded [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The post-operative range of motion after bony stabilization of the glenoid has been under debate lately [25,31] patients after open Latarjet procedures [12]. Additionally, a biomechanic evaluation by Giles et al demonstrated a significant loss of high external rotation after Latarjet procedures in a cadaveric model when the conjoint tendon was loaded [17].…”
Section: Discussionmentioning
confidence: 99%
“…The post‐operative range of motion after bony stabilization of the glenoid has been under debate lately [25, 31]. A recent study by Sinha et al could demonstrate a significant loss of abduction, forward flexion, external rotation and internal rotation after the open Latarjet procedure, whereas the muscle strength was not impaired [33].…”
Section: Discussionmentioning
confidence: 99%
“…Osteoarthritis on long-term follow-up in the glenohumeral joint after traditional Latarjet procedure is a concern, and prominent bone block or metal-ware are the major attributed causes. 14 Osteolysis of the superior aspect of the transferred coracoid bone after Latarjet is a common phenomenon, 16,17 and this can make the screw heads used for Latarjet procedure more prominent. Cohen et al 16 report an incidence of osteolysis of up to 57.8%, although this did not affect the long-term outcome significantly.…”
Section: Discussionmentioning
confidence: 99%
“…This capsular reattachment on to the glenoid rim [Fig: 10A] helps to exteriorize the coracoid bone (Fig 10C ) and further aids in preventing inferior wear on humeral head reported in previous long-term studies of Latarjet procedure. 14 Tips and tricks for this technique are given in Table 3, and pearls and pitfalls in Table 4. 15 The limitations and risks of this procedure are described in Table 5.…”
Section: Capsulolabral Complex Repair With Suture Anchorsmentioning
confidence: 99%
See 1 more Smart Citation